Improving Students' Understanding of Islamic Education Learning through Value-Based Learning Approach at SMP Negeri 2 Hutauraja Tinggi - Lubis, Monang; Pasaribu, Tilam; Suprihati (Indonesian Journal of Education and Social Humanities, 2024)
This study aims to improve students' understanding of Islamic religious education learning through the Value-Based Learning Approach. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were junior high school students. The data for this study were obtained using test and observation techniques. Tests are used to measure learning and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that through the Value-Based Learning Approach, students' understanding of Islamic religious education learning can be improved. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 40.89%, the first cycle 68.87% and in the second cycle it increased to 90.32%. Thus, through the Value-Based Learning Approach can be used as an alternative to improve students' understanding of Islamic religious education learning.